Periodontal disease during pregnancy and low birth weight of newborns at Chris Hani district of Eastern Cape - Ayo-Yusuf, Olalekan Abdulwahab (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2013.